Pembuktian Empiris dan Validasi Alternatif dalam Kajian Hadis Kontemporer - Akmaluddin, Muhammad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2021)
The discovery of various manuscripts, the offer of new theories, the paradigm shifts, the popularity of studies and so on have highlighted the journey of hadith studies from time to time. The study of hadith should continue to develop, by not detaching itself from the previous legacy (waṣl) and by not neglecting contextualization and dialogue with the development of other sciences (faṣl). By using a qualitative approach, literature review and content analysis, this paper examines the dialectic of thesis and antithesis of hadith studies with empirical research related to isnād and matn. In addition, this paper also gives an offer to use alternative validation to authenticate hadith. Archaeological studies, external evidence from non-Islamic sources, historical reports from non-Muslims and cons have also highlighted the studies carried out by revisionist and traditionalist schools. Alternative validation of hadith can be traced through alternative proof of isnād with i‘tibar al-asānīd on hadith that are considered as week, or through abstraction of hadith and living hadith which reflects the phenomena of texts which made concise and lived in society. Penemuan berbagai manuskrip, tawaran teori baru, pergeseran paradigma, popularitas kajian dan lain sebagainya ikut mewarnai perjalanan kajian hadis dari waktu ke waktu. Kajian hadis harus tetap berkembang, dengan tidak melepaskan dirinya dari pijakan warisan terdahulu (waṣl) dan tidak mengabaikan kontekstualisasi dan dialog dengan perkembangan ilmu pengetahuan lain (faṣl). Dengan menggunakan pendekatan kualitatif, kajian literatur dan analisis konten, makalah ini akan mengkaji tentang dialektika tesis dan antitesis kajian hadis dengan penelitian empiris yang berkaitan dengan isnād dan matn. Di samping itu, tulisan ini juga memberikan tawaran untuk menggunakan validasi alternatif terhadap otentikasi suatu hadis. Kajian arkeologis, pembuktian eksternal dari sumber-sumber non-Islam, laporan historis dari non-Muslim dan kontra ikut mewarnai kajian yang dilakukan aliran revisionis dan tradisionalis. Validasi alternatif hadis dapat melalui pembuktian alternatif isnād dengan i‘tibar al-asānīd atas hadis-hadis yang dianggap daif, serta abstraksi hadis dan living hadis yang merupakan fenomena teks yang dibuat ringkas dan hidup di dalam masyarakat.